Gait speed as an incremental predictor of mortality and major morbidity in elderly patients undergoing cardiac surgery - Afilalo, Jonathan; Eisenberg, Mark J; Morin, Jean-François; Bergman, Howard; Monette, Johanne; Noiseux, Nicolas; Perrault, Louis P; Alexander, Karen P; Langlois, Yves; Dendukuri, Nandini; Chamoun, Patrick; Kasparian, Georges; et al. (Journal of the American College of Cardiology, 2010)
The purpose of this study was to test the value of gait speed, a clinical marker for frailty, to improve the prediction of mortality and major morbidity in elderly patients undergoing cardiac surgery. It is increasingly difficult to predict the elderly patient's risk posed by cardiac surgery because existing risk assessment tools are incomplete. A multicenter prospective cohort of elderly patients undergoing cardiac surgery was assembled at 4 tertiary care hospitals between 2008 and 2009. Patients were eligible if they were 70 years of age or older and were scheduled for coronary artery bypass and/or valve replacement or repair. The primary predictor was slow gait speed, defined as a time taken to walk 5 m of ≥ 6 s. The primary end point was a composite of in-hospital post-operative mortality or major morbidity. The cohort consisted of 131 patients with a mean age of 75.8 ± 4.4 years; 34% were female patients. Sixty patients (46%) were classified as slow walkers before cardiac surgery. Slow walkers were more likely to be female (43% vs. 25%, p = 0.03) and diabetic (50% vs. 28%, p = 0.01). Thirty patients (23%) experienced the primary composite end point of mortality or major morbidity after cardiac surgery. Slow gait speed was an independent predictor of the composite end point after adjusting for the Society of Thoracic Surgeons risk score (odds ratio: 3.05; 95% confidence interval: 1.23 to 7.54). Gait speed is a simple and effective test that may identify a subset of vulnerable elderly patients at incrementally higher risk of mortality and major morbidity after cardiac surgery.